BIOSYSTEMATIC STUDIES IN SOME NIGERIAN SPECIES OF ANTHERICUM LIN. AND CHLOROPHYTUM KER-GAWL. (LILIACEAE) (1981)
Field surveys and investigations of representatives of Anthericum L. and Chiprophytum Ker-Gawl. complex in Nigeria were carried out in their natural habitats in at least sixteen States of the Nigerian Federation. All herbarium specimens in the Forestry Research Institute, Ibadan and in nine Nigerian Univetfsities visited were examined (if any). So far, ten species of Anthericum and fifteen species of Chlorophytum have been reported and collected in Nigeria. They were all studied morphologically. Detailed ecological analyses including the Chemical composition of their soils were carried out on three taxa of Anthericum and ten taxa of Chrolophytum. Many living populations were sampled from their different natural habitats in Nigeria, Their representatives were cultivated in three locations for experimental studies. Data were collected on the morphology by conventional methods and analysed. Anatomical data were amassed from the leaf surface patterns and the roots. Types of leaf margin anatomy were noted. Cytological studies were carried out in five taxa of Anthericum and eleven taxa of Chlorophytum. There were inter-generic hybridization tests. The use of lea f vein spacing interval and anther: filament ratio as taxonomic criteria have been suggested and their usefulness in the monocotyledon taxonomy, especially in Liliaceae, needed to be further explored. The importance of leaf margin anatomy as a taxonomic criterion above species level was highlighted. Chromosome counts for seven taxa were confirmed, viz; C. macrophvllum (A. Rieh.) Aschers 2n = 28. C. blepharophvllum gchwinf. ex Bak. 2n = 28. C. atenopetalum I Bak. 2n = 14. C. atenopetalum II (sp. nov.) 2n = 14. C. laxum R. Br. 2n = 14. C. inomatum Ker-Gawl. 2n = 14. C. togoense Engl. 2n = 14. New chromosome counts were recorded in :- C. geophilum Peter ex. v. Poelln. 2n = 28. C. alisaifolium Bak. 2n = 16. Chiprophytum X ( related to C. elatum ) 2n = 16. C . caulescens (Bak.) Marais & Reilly ( formerly A. caulescens Bak.) 2n = 16. A. Limosum Bak. 2n = 16. A. pterooaulon I Welw. ex Bak 2n = 24. A. Pterocaulon II 2n = 16. A. nubicum Bak. 2n = 16. A. pubirhachis Bak. 2n = 16. A. uvuiense 2n = 16. The possible evolution o f chromosome numbers in the complex has been postulated. The possible chromosome evolution o f the complex based on the available data from this work and existing literature has been proposed. Evidence was adduced to Support the Suggestion that the possible basic Chromosome number in the complex was x = 4, and that n = 8 Was a secondary basic number. It has also been contended that n =7 and n= 6 evolved from a more primitive n = 8. Supplementary evidence in Support of Marais and Reilly’ s (1978) transfer of A. caulescens from Anthericum into Chloronhytum as C. caulescens was adduced. A form of C.stenopetalum has been elevated to species level on account of its morphological, cytological and genetic differences. A new taxonomic key has been proposed for the Separation of Anthericum and Chiprophytum. The possible mode of evolution of some Nigerian species of Anthericum and Chlorophytum. based mainly on their leaf surface patterns, has been proposed.